Composition of Gut Microbiota Influences Resistance of Newly Hatched Chickens to Salmonella Enteritidis Infection - Varmuzova, Karolina; Kubasova, Tereza; Davidova-Gerzova, Lenka; Sisak, Frantisek; Havlickova, Hana; Sebkova, Alena; Faldynova, Marcela; Rychlik, Ivan (Frontiers in Microbiology, 2016)
Since poultry is a very common source of non-typhoid Salmonella for humans, different interventions aimed at decreasing the prevalence of Salmonella in chickens are understood as an effective measure for decreasing the incidence of human salmonellosis. One such intervention is the use of probiotic or competitive exclusion products. In this study we tested whether microbiota from donor hens of different age will equally protect chickens against Salmonella Enteritidis infection. Newly hatched chickens were therefore orally inoculated with cecal extracts from 1-, 3-, 16-, 28- and 42-week-old donors and 7 days later, the chickens were infected with S. Enteritidis. The experiment was terminated 4 days later. In the second experiment, groups of newly hatched chickens were inoculated with cecal extracts of 35-week-old hens either on day 1 of life followed by S. Enteritidis infection on day 2 or were infected with S. Enteritidis infection on day 1 followed by therapeutic administration of the cecal extract on day 2 or were inoculated on day 1 of life with a mixture of the cecal extract and S. Enteritidis. This experiment was terminated when the chickens were 5 days old. Both Salmonella culture and chicken gene expression confirmed that inoculation of newly hatched chickens with microbiota from 3-week-old or older chickens protected them against S. Enteritidis challenge. On the other hand, microbiota from 1-week-old donors failed to protect chickens against S. Enteritidis challenge. Microbiota from 35-week-old hens protected chickens even 24 hours after administration. However, simultaneous or therapeutic microbiota administration failed to protect chickens against S. Enteritidis infection. Gut microbiota can be used as a preventive measure against S. Enteritidis infection but its composition and early administration is critical for its efficacy.